2011
DOI: 10.1007/s00894-011-1253-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation of water removal from simple gases with zeolite NaA

Abstract: Water vapor removal from some simple gases using zeolite NaA was studied by molecular simulation. The equilibrium adsorption properties of H(2)O, CO, H(2), CH(4) and their mixtures in dehydrated zeolite NaA were computed by grand canonical Monte Carlo simulations. The simulations employed Lennard-Jones + Coulomb type effective pair potential models, which are suitable for the reproduction of thermodynamic properties of pure substances. Based on the comparison of the simulation results with experimental data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Hydrophilic zeolites have a good adsorption capacity for water, high thermal stability, and regeneration temperature higher than 220 °C . Zeolites Linde Type A (LTA) and Faujasite (FAU) were widely used for water adsorption, and especially for water‐alcohol mixture separation at temperatures lower than 100 °C . Only very few experimental studies were found including adsorption data at high temperatures (up to 200 °C) but most of them focused on membrane permeation for gases separation or molecular sieving [14,19–22] and were not oriented toward adsorption studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophilic zeolites have a good adsorption capacity for water, high thermal stability, and regeneration temperature higher than 220 °C . Zeolites Linde Type A (LTA) and Faujasite (FAU) were widely used for water adsorption, and especially for water‐alcohol mixture separation at temperatures lower than 100 °C . Only very few experimental studies were found including adsorption data at high temperatures (up to 200 °C) but most of them focused on membrane permeation for gases separation or molecular sieving [14,19–22] and were not oriented toward adsorption studies.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Zeolites Linde Type A (LTA) and Faujasite (FAU) were widely used for water adsorption, and especially for water-alcohol mixture separation at temperatures lower than 100 8C. [11][12][13][14][15][16][17][18][19] Only very few experimental studies were found including adsorption data at high temperatures (up to 200 8C) but most of them focused on membrane permeation for gases separation or molecular sieving [14,[19][20][21][22] and were not oriented toward adsorption studies. Works at higher temperatures (up to 310 8C) concern modelling and simulation only.…”
Section: Introductionmentioning
confidence: 99%
“…In these models, the interaction sites were fixed at their experimental atomic positions and assigned their Lennard-Jones energy (ε) and size (σ) parameters, as well as point charges (q). For zeolite NaA, the model that was developed earlier was modified slightly [14] by adding weak Lennard-Jones interaction sites with realistic size parameters [16,19] to the (originally) pure Coulombic silicon and aluminium atoms, thus preserving the dominant role of oxygen atoms in the dispersion interactions of the framework. For hydrogen sulphide, a rigid four-site model proposed recently by Shah et al [20] was adopted, in which the location of the charge parameter of the sulphur atom is offset on the HSH angle bisector towards the hydrogen atoms.…”
Section: Models and Simulation Detailsmentioning
confidence: 99%
“…The adsorption and separation properties of zeolite NaA have already been examined in several experimental [2][3][4][5][6] and theoretical/simulation [7][8][9][10][11][12][13][14][15][16] works. In our laboratories, the adsorption characteristics of zeolite NaA and its performance as a drying agent by classical atomistic simulations [10,[12][13][14] were studied, and new intermolecular potential models for this zeolite [12][13][14] proposed. Our models were optimized for the study of the selective adsorption of water from its mixtures with less polar or non-polar molecules like simple alcohols, carbon monoxide, hydrogen and methane.…”
Section: Introductionmentioning
confidence: 99%
“…However, the complexity of zeolite frameworks as well as the presence of various nontetrahedral cations at different sites significantly hinder the interpretation of their vibrational spectra, particularly when investigating ion exchange in zeolites. For these reasons, computational methods have become the second most important tool for performing detailed analysis of structural properties and interpreting vibrational spectra [2,[12][13][14][15][16][17]. On the other hand, the complexity of zeolite systems limits the application of computational methods to these systems.…”
Section: Introductionmentioning
confidence: 99%